MD2 Inhibits Choroidal Neovascularization via Antagonizing TLR4/MD2 Mediated Signaling Pathway. (4th May 2023) - Wu, Qi; Chen, Zhang; Wu, Chenxin; Zhang, Lingxi; Wu, Yuyang; Liu, Xiyuan; Wang, Yi; Zhang, Zongduan
Abstract: Purpose: To explore the pathological mechanism of Toll-like receptor 4 (TLR4) mediating neovascular age-related macular degeneration (nAMD) and the potential role of the TLR4 coreceptor myeloid differentiation protein 2 (MD2). Methods: In the study, we inhibited MD2 with the chalcone derivative L2H17 and we utilized a laser-induced choroidal neovascularization (CNV) mouse model and Tert-butyl hydroperoxide (TBHP)-challenged rhesus choroid-retinal endothelial (RF/6A) cells to assess the effect of MD2 blockade on CNV. Results: Inhibiting MD2 with L2H17 reduced angiogenesis in CNV mice, and significantly protected against retinal dysfunction. In retina and choroid/retinal pigment epithelium (RPE) tissues, L2H17 reduced phospho-ERK, phospho-P65 but not phospho-P38, phospho-JNK, and reduced the transcriptional levels of IL-6, TNF-α, ICAM-1 but not VCAM-1. L2H17 could protect RF/6A against TBHP-induced inflammation, oxidative stress, and apoptosis, via inhibiting the TLR4/MD2 signaling pathway and the following downstream mitogen-activated protein kinase (MAPK) and nuclear transcription factor-κB (NF-κB) activation. Conclusions: Inhibiting MD2 with L2H17 significantly reduced CNV, suppressed inflammation, and oxidative stress by antagonizing TLR4/MD2 pathway in an MD2-dependent manner. MD2 may be a potential therapeutic target and L2H17 may offer an alternative treatment strategy for nAMD.